Profesi Konselor dalam Kurikulum 2013 dan Permasalahannya - Wibowo, Mungin Eddy (Guidance and Counseling Study Program, Pattimura University, 2017)
Implementation of the 2013 curriculum will create problems for high school learners who can not afford in choosing the right direction of subject groups and subjects appropriately, so that will cause difficulties in learning and tendency to fail in learning. The determination of the direction of the subject group and the subjects should be in accordance with the general basic skills (intelligence), talents, interests and preferences of each learner so that the learning process goes well and the tendency to succeed in learning. Therefore, the guidance and counseling service in the direction of the subject group and the subject is very necessary for the learner to be able to make choices according to his potential ability and the possibility of success in learning.